DIGITAL LITERACY BASED CURRICULUM DEVELOPMENT AS AN ADAPTIVE RESPONSE TO TECHNOLOGICAL DISRUPTION AT KH. ABD. WAHAB HASBULLAH JOMBANG'S LEADING ISLAMIC HIGH SCHOOL - M. Aliyul Wafa; Saihul Atho Alaul Saihul Atho Alaul; Khoirun Nisa; Muhammad Fodhil (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: Technological disruption demands that Islamic schools (madrasahs) design curricula that integrate digital literacy, Islamic values, and Islamic boarding school culture to shape students' religious character. Previous research has examined curriculum management for graduate quality control, but has not yet operationalized digital literacy or provided a theoretical basis for Islamic boarding school integration. Purpose of the Study: This study aims to analyze the planning, implementation, and evaluation of a digital literacy-based curriculum at the KH. Abd. Wahab Hasbullah Islamic Boarding School in Jombang, and to theoretically explain the role of Islamic educational values, Islamic boarding school culture, and religious character formation in shaping the curriculum design. Methods: The study employed a qualitative approach with a single case study design based on fieldwork. Data were collected through participant observation, semi-structured interviews, and documentation. Data were analyzed using the Miles-Huberman-Saldana interactive model. Their validity was tested through triangulation of sources, techniques, and time. Results: Curriculum development involves three integrated stages: participatory planning based on the madrasah's vision and mission, implementation of six flagship programs with digital competency strengthening, and multi-layered evaluation. Digital literacy emphasizes interactive media and information access and evaluation, conceptually distinct from administrative technologies such as CCTV and digital attendance. Conclusions: This madrasah curriculum model integrates digital literacy and Islamic boarding school values ​​within a tiered management system; without empirical impact testing, claims of improved graduate quality are interpreted as potential contributions, not proven causal relationships.